Insights on the origin of multiple tsunami events affected the archaeological site of Ognina (south-eastern Sicily, Italy). (20th November 2022) - Scardino, Giovanni; Rizzo, Angela; De Santis, Vincenzo; Kyriakoudi, Despo; Rovere, Alessio; Vacchi, Matteo; Torrisi, Salvatore; Scicchitano, Giovanni
Abstract: South-eastern Sicily is one of the most seismically active areas of the Mediterranean Sea, marked by a high level of crustal seismicity, causing major earthquakes (up to Mw ∼7). As a consequence, this area is prone to earthquake-generated tsunamis, which affected the Ionian coast of Sicily in historical times. These tsunamis left geomorphic and sedimentary imprints, such as large boulders or high-energy deposits, along the coasts. One of these was reported by previous works along the coast of Ognina, a small residential area located 20 km south of Siracusa. The deposits ﬁll the back edge of a ria incised into Miocene limestones, are composed of three main stratigraphic units and were attributed to several tsunami and storm events that occurred along the coasts of south-eastern Sicily since the IV century Common Era (CE). Here, we use numerical models to simulate the impact of these extreme marine events, at the time of their occurrence, along the Ognina coastal sector, with the aim to: i) better define the tsunamigenic sources responsible for the events found in the deposits, ii) verify if some units could be related to a storm event, iii) investigate constrains on the paleogeography of the studied area at the time of tsunami and storm occurrence. We reconstructed the morphology of ancient local landscapes using geological and historical information, together with a detailed topographic and geoelectrical survey. We implemented a modelling chain (composed of Delft Dashboard, Delft 3d-FLOW and XBeach) to simulate the tsunami and storm wave propagation upon the ancient landscapes. Our results demonstrate that the use of advanced modeling tools, combined with in situ geological evidence and geophysical survey, has the potential to support the attribution of coastal geomorphic imprints to specific tsunami or storm events, the better definition of the paleo-landscapes, and the identification of the most likely tsunamigenic sources. This last aspect plays a fundamental role in providing more reliable characteristics of the tsunami propagation as well as in the assessing of potential tsunami hazard and related coastal impacts.